Supplementation of a tropical low-quality forage with Calliandra calothyrsus improves sheep health and performance, and reduces methane emission - Mwangi, Paul M.; Eckard, Richard; Gluecks, Ilona; Merbold, Lutz; Mulat, Daniel Girma; Gakige, Jesse; Marquardt, Svenja; Pinares-Patino, Cesar S. (Frontiers in Animal Science, 2024)
Ruminant production systems in the arid and semi-arid regions of Sub-Saharan Africa confront severe challenges due to recurring droughts and the intensifying effects of climate change (CC). These systems grapple with numerous stress factors, including poor animal nutrition, water scarcity, gastrointestinal (GIT) parasite burdens, and heat stress, which contribute to below optimal animal productivity and a high environmental footprint. Addressing these issues urgently, by creating livestock systems resilient to CC that also promote better animal health, enhanced productivity, and reduced environmental impact, is paramount to safeguarding the livelihoods of the rural population. This 50-day study aimed to evaluate the effects of improved feeding and nutritional management in sheep, focusing on GIT parasite infections, feed intake and digestibility, liveweight (LW) gain, and enteric methane (CH4) emissions. We investigated the legume forage tree, Calliandra (Calliandra calothyrsus), as a high-quality feed source because of its rich crude protein content and its potential as a remedy for gastrointestinal tract (GIT) parasite infections, attributed to its high condensed tannin (CT) content. Twenty-eight Dorper lambs underwent random allocation across four treatments, each consisting of seven lambs. These treatments combined either a trickle infection or no infection with Haemonchus contortus with a supplementation (40% of diet on a dry matter basis or lack thereof) of the basal diet (Rhodes grass hay) with dried Calliandra leaflets. The treatments were: UnHay (uninfected, fed on hay-only), InHay (infected, fed on hay-only), InHay+Cal (infected, fed on hay plus Calliandra), and InHay+Cal+PEG [infected, fed on hay, Calliandra, and polyethylene glycol (PEG)]. The latter was to evaluate the potential effects of Calliandra’s condensed tannins. The results show that lambs in the InHay+Cal treatment exhibited a higher packed cell volume (PCV) and lower faecal egg counts (FEC) compared to the InHay group. No effects of infection on the other measured variables were observed in unsupplemented lambs. Calliandra supplementation increased total feed dry matter intake (DMI) by 20% (61.8 vs. 51.7 g DM/kg LW0.75) (InHay+Cal vs. InHay) and enhanced LW gain (7.2 g/d) in the InHay+Cal group, whereas the unsupplemented infected group (InHay) experienced LW loss (-26.6 g/d). Calliandra supplementation to infected lambs reduced daily CH4 emission by 15% (13.9 vs. 16.2 g/d) and CH4 yield (g/kg DMI) by 30% (18.7 vs. 26.5 g/kg DMI), compared to emissions from unsupplemented infected lambs. Nonetheless, Calliandra supplementation decreased the digestibility of crude protein and fibre and raised the faecal nitrogen (N) output to N intake (FN/NI) ratio. The effects of PEG supplementation on CT activity remained inconclusive. The study concludes that a 40% replacement of a protein-deficient basal diet with Calliandra may be excessive. However, the findings underscore the considerable advantages of integrating Calliandra into farming systems. Such nature-based solution control GIT parasite infections and their lifecycle, bolster the nutritional value of a deficient basal diet, improve animal productivity cost-effectively, and mitigate enteric methane emissions both in absolute terms and intensity.